Chemical Composition of Artemisia argyi Extract (RW0117) and Protective Effects against Gastric Lesions in vivo - Lee, Jin-Woo; Lee, Il Kyun; Park, Se-Hoon; Chang, Min Jegal; Choi, Keun Young; Jung, Hye Young; Choi, Jung A; Lee, Chan-Kyu; Kim, Ho Kyong; Lee, Jung Suk (Natural product sciences, 2020)
In this study, we investigated the chemical profile and effects of RW0117 (Artemisia argyi 65.5% ethanol extract) on gastric lesions in rats. We optimized and validated a method to obtain the chemical profile of RW0117. We then investigated the antioxidant and anti-inflammatory effects in vitro, and the protective effects on gastric lesions in vivo. The IC50 of 2,2-diphenyl-1-picrylhydrazyl free radical scavenging considering the antioxidant effects of RW0117 was 166.55 μg/mL, and the IC50 of nitric oxide scavenging considering the anti-inflammatory effects was 41.16 μg/mL. Oral administration of RW0117 at lower concentrations (25, 50, 100 mg/kg) had similar or greater effects than the daily intake conversion concentration (115 mg/kg) of a health functional food (Avexol®) in the acetic acid-induced ulcer and the ethanol-induced gastric injury rat models. In addition, oral administration of RW0117 increased the expression of prostaglandin E2, which enhances the protective effect in the gastric mucosa in the ethanol-induced gastric injury rat model. These results suggest that RW0117 may have potential therapeutic uses in the protection of the gastric mucosa. KCI Citation Count: 0